Experimental study and modelling of unsteady aerodynamic forces and moment on flat plate in high amplitude pitch ramp motion. (3rd May 2018) - Yu, Yuelong; Amandolese, Xavier; Fan, Chengwei; Liu, Yingzheng
Abstract : This paper examines the unsteady lift, drag and moment coefficients experienced by a thin airfoil in high-amplitude pitch ramp motion. Experiments have been carried out in a wind tunnel at moderate Reynolds number ( $Re≈ 1.45× 10^{4}$ ), using a rigid flat-plate model. Forces and moments have been measured for reduced pitch rates ranging from 0.01 to 0.18, four maximum pitch angles ( $30^{° }, 45^{° }, 60^{° }, 90^{° }$ ) and different pivot axis locations between the leading and the trailing edge. Results confirm that for reduced pitch rates lower than 0.03, the unsteady aerodynamics is limited to a stall delay effect. For higher pitch rates, the unsteady response is dominated by a buildup of the circulation, which increases with the pitch rate and the absolute distance between the pivot axis and the $3/4$ -chord location. This circulatory effect induces an overshoot in the normal force and moment coefficients, which is slightly reduced for a flat plate with a finite aspect ratio close to 8 in comparison with the two-dimensional configuration. A new time-dependent model has been tested for both the normal force and moment coefficients. It is mainly based on the superposition of step responses, using the Wagner function and a time-varying input that accounts for the nonlinear variation of the steady aerodynamics, the pivot point location and an additional circulation which depends on the pitch rate. When compared with experiments, it gives satisfactory results for $0^{° }$ to $90^{° }$ pitch ramp motion and captures the main effect of reduced pitch rate and pivot point location.